2010
DOI: 10.1021/jm100482n
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Tricyclic Benzoxazines as Potent 5-HT1A/B/D Receptor Antagonists Leading to the Discovery of 6-{2-[4-(2-methyl-5-quinolinyl)-1-piperazinyl]ethyl}-4H-imidazo[5,1-c][1,4]benzoxazine-3-carboxamide (GSK588045)

Abstract: Bioisoteric replacement of the metabolically labile N-methyl amide group of a series of benzoxazinones with small heterocyclic rings has led to novel series of fused tricyclic benzoxazines which are potent 5-HT(1A/B/D) receptor antagonists with and without concomitant human serotonin transporter (hSerT) activity. Optimizing against multiple parameters in parallel identified 6-{2-[4-(2-methyl-5-quinolinyl)-1-piperazinyl]ethyl}-4H-imidazo[5,1-c][1,4]benzoxazine-3-carboxamide (GSK588045) as a potent 5-HT(1A/B/D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Using our method, the reaction between hydrazine, 2‐formylbenzoic acid, and TMSN 3 permitted the construction of tetrazolo[5,1‐ a ]phthalazine in one step in 48 % yield. Next, we attempted the synthesis of 4 H ‐benzo[ b ]tetrazolo[1,5‐ d ][1,4]oxazine, which is an antidepressant/anxiolytic agent 21. Treating 2‐aminophenol with 2‐chloroacetyl chloride in the presence of TMSN 3 allowed the preparation of a tetrazole ring fused to a benzooxazine (Table 2, entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…Using our method, the reaction between hydrazine, 2‐formylbenzoic acid, and TMSN 3 permitted the construction of tetrazolo[5,1‐ a ]phthalazine in one step in 48 % yield. Next, we attempted the synthesis of 4 H ‐benzo[ b ]tetrazolo[1,5‐ d ][1,4]oxazine, which is an antidepressant/anxiolytic agent 21. Treating 2‐aminophenol with 2‐chloroacetyl chloride in the presence of TMSN 3 allowed the preparation of a tetrazole ring fused to a benzooxazine (Table 2, entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…A number of new hetero-tricyclic ring systems were synthesized by Bromidge and co-workers, such as fused imidazolo, triazolo, and tetrazolo-benzoxazines, to study the effect on the binding affinity to the receptor. [139] Methods for a rapid and efficient synthesis of new 3-m-[1,2,3]triazol-3-deoxythymidine analogues (76) from AZT under Huisgen conditions was described by Lin et al [140] The new analogues showed higher efficiencies (K m /V max values) in all cases with Ureaplasma parvum thimidine kinase (UpTK) than with human cytosolic thymidine kinase (hTK1). Structural models of UpTK and hTK1 were constructed and used to explain the kinetic results.…”
Section: Antifungal and Antibacterialsmentioning
confidence: 99%
“…In a series of compounds synthesized by Leslie et al, compound 105 emerged as the most potential candidate for antidepressant activity [186]. Compound 106 was reported as a potent 5-HT 1A/B/D receptor antagonist by Bromidge et al [187]. Andersen et al discovered compound 107 as a treatment strategy for major depressive disorder [188].…”
Section: Antidepressant Activitymentioning
confidence: 99%